Degree of phosphorus saturation threshold for minimizing P losses by runoff in cropland soils of Southern Brazil - Bortolon, Leandro; Ernani, Paulo Roberto; Bortolon, Elisandra Solange Oliveira; Gianello, Clesio; Almeida, Rodrigo Gabriel Oliveira de; Welter, Samuel; Rogeri, Douglas Antônio (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to assess the risk of phosphorus losses by runoff through an index based on the degree of P saturation (DPS), in cropland soils of Southern Brazil. Sixty-five highly representative cropland soils from the region were evaluated. Three labile P forms were measured (Mehlich-1, Mehlich-3, and ammonium oxalate), and four P sorption indexes were tested (phosphorus single sorption point and Fe+Al determined with the three extractors). Water- extractable P (WEP) was used as an index of P susceptibility to losses by surface runoff. The DPS was determined from the ratio between labile P and each sorption index. DPS values obtained from the ratio between Mehlich-1 P and the single P sorption point ranged from 1 to 25%, whereas those from Mehlich-1 P and Fe+Al (ammonium oxalate) ranged from 1 to 55%. All DPS types were highly correlated with WEP. From a practical stand point, the DPS obtained with both P and Fe+Al extracted with Mehlich-1 can be used to estimate the risk of P losses by runoff in soils of Southern Brazil.